In Situ Silver‐Based Electrochemical Oncolytic Bioreactor (Adv. Mater. 40/2022). Issue 40 (6th October 2022) - Huang, Yong; Zhong, Liping; Li, Xiaotong; Wu, Pan; He, Jian; Tang, Chao; Tang, Zhiping; Su, Jing; Feng, Zhenbo; Wang, Bing; Ma, Yun; Peng, Hongmei; et al.
Abstract : Bioreactors In article number 2109973, Liping Zhong, Kun Zhang, Yongxiang Zhao, and co‐workers describe how a tumor‐microenvironment‐enabled in situ silver‐based electrochemical oncolytic bioreactor (SEOB) unlocks antitumor Ag + prodrugs for highly efficient subcutaneous and orthotopic tumor recession via activating production of reactive oxygen species (ROS). Reduced graphene oxide (rGO), featuring 20‐fold larger catalysis rate than GO, allows intratumoral H2 O2 as reductants to reduce Ag + into silver nanoparticles especially after uniting with vitamin‐C‐mediated H2 O2 production.